Ultrafast quantum key distribution using fully parallelized quantum channels - Terhaar, Robin; Rödiger, Jasper; Häußler, Matthias; Wahl, Michael; Gehring, Helge; Wolff, Martin A.; Beutel, Fabian; Hartmann, Wladick; Walter, Nicolai; Hanke, Jonas; Hanne, Peter; Walenta, Nino; et al. (Optics express, 2023)
The field of quantum information processing offers secure communication protected by the laws of quantum mechanics and is on the verge of finding wider application for the information transfer of sensitive data. To improve cost-efficiency, extensive research is being carried out on the various components required for high data throughput using quantum key distribution (QKD). Aiming for an application-oriented solution, we report the realization of a multichannel QKD system for plug-and-play high-bandwidth secure communication at telecom wavelengths. We designed a rack-sized multichannel superconducting nanowire single photon detector (SNSPD) system, as well as a highly parallelized time-correlated single photon counting (TCSPC) unit. Our system is linked to an FPGA-controlled QKD evaluation setup for continuous operation, allowing us to achieve high secret key rates using a coherent-one-way protocol.
Gesehen am 20.03.2023